Mekanisme Survival Buruh Harian Penebang Kayu di Desa Muara Pari, Kecamatan Lahei, Kabupaten Barito Utara - Novri Amdani Saragih; Saputra Adiwijaya; Ida Bagus Suryanatha (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study analyzes the survival mechanisms of daily wage timber-cutting laborers in Muara Pari Village, Lahei District, Barito Utara Regency, an indigenous Dayak Taboyan community whose livelihood structure has shifted from agrarian subsistence toward extractive-sector labor as mining, plantation, and timber concessions increasingly encircle the village's forest and land, compounded by fluctuating commodity prices, positioning the study within the broader problem of rural economic precarity amid extractive-industry expansion. The study aims to analyze the forms of survival mechanisms laborers employ to manage economic vulnerability amid this encirclement. Using a descriptive qualitative approach with in-depth interviews and secondary data, the study applies James C. Scott's moral economy theory and safety-first principle as its analytical framework. Findings show that laborers' vulnerability stems from restricted access to natural capital, compounded by rubber prices collapsing below Rp7,000 per kilogram and high logistics costs from poor road access, prompting three survival strategies: belt-tightening, dual-livelihood diversification, and the use of social networks through the Handep tradition and patron-client relations. Strong social capital and a village policy opening access to former rubber-plantation land are the main pillars keeping laborers above the subsistence crisis line, affirming the continued relevance of Scott's peasant subsistence logic today.